Implications of a Family History of Diabetes and Rapid eGFR Decline in Patients With Type 2 Diabetes and Biopsy-Proven Diabetic Kidney Disease - Wang, Yiting; Zhao, Lijun; Zhang, Junlin; Wu, Yucheng; Zhang, Rui; Li, Hanyu; Guo, Ruikun; Han, Qianqian; Wang, Tingli; Li, Lin; Wang, Shanshan; Liu, Fang (Frontiers in Endocrinology, 2019)
Objective: This study aimed to identify the risk factors for a rapid decline in the estimated glomerular filtration rate (eGFR) in Chinese patients with type 2 diabetes and biopsy-proven diabetic kidney disease (DKD). Method: This was a retrospective cohort study. Patients with biopsy-proven DKD who had been followed-up for at least 1 year were enrolled. Baseline clinicopathological data and serum creatinine levels that had been measured at least three times during follow-up in our hospital were collected. Patients were allocated to two groups of rapid decliners and slow decliners according to the median eGFR slope. The associations between potential risk factors and rapid eGFR decline were analyzed using logistic regression. Results: A total of 128 eligible patients were enrolled and they had a mean age of 51.5 ± 10.7 years. During a median follow-up of 2 years, the median eGFR slope was −8.1 ± 14.4 mL/min/1.73 m2/year. The eGFR decline was significantly faster in patients with a family history of diabetes in first-degree relatives, nephrotic-range proteinuria, higher grades of glomerular pathology, and interstitial inflammation. No differences in the rate of the eGFR decline were observed in subgroups created according to sex, age, hypertension, glycosylated hemoglobin, diabetic retinopathy, interstitial fibrosis, and tubular atrophy. Logistic regression indicated that a family history of diabetes was independently associated with a rapid decline in eGFR, even after adjustment for factors including baseline eGFR and proteinuria. Conclusion: A family history of diabetes in first-degree relatives is independently associated with a rapid decline in eGFR in the current relatively young studied patients. Our findings suggested that early diagnosis and treatment is important for these patients.